Corrosion Property Analysis of Coating Formulated Using Acrylic Polyol and Silicone Resin Hybrid Systems - Jamari, S.K.M.; Ramesh, Kasi; Vengadaesvaran, Balakrishnan; Ramesh, Subramaniam; Rau, S.R.; Arof, Abdul Kariem (2013)
Coating systems consist of acrylic polyol resin and silicone intermediate resins were tested for their corrosion resistance properties. The corrosion protection property of the coating was evaluated by using Electrochemical Impedance Spectroscopy (EIS) which showed that system with 70 % of acrylic has the highest corrosion resistance. The maximum value of corrosion resistance obtained was found to be 1.40 x 109 Ω on the 30th day for the 70 % of acrylic sample. The glass transition temperature (Tg) obtained using the Differential Scanning Calorimetry (DSC) were in the range of 23 °C to 65 °C. It showed that all samples are suitable for decorative paints, general industrial coatings and floor care coatings. The functional groups and also the cross-linking between the organic resins were analyzed using Fourier Transform Infra-Red Spectroscopy.